2014
DOI: 10.5812/ircmj.18797
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress in Physicians Practicing in Hospitals Affiliated to Medical Sciences Universities

Abstract: Background:Researchers have regarded moral distress as a major concern in the health care system. Symptoms associated with moral distress may manifest as frustration, dissatisfaction, and anxiety and may lead to burnout, job leaving, and finally, failure to provide safe and competent care to patients. Proper management of this phenomenon can be fulfilled through study of its causes at different levels of health services and taking necessary measures to solve them.Objectives:This study aimed to determine the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(75 citation statements)
references
References 37 publications
3
71
1
Order By: Relevance
“…In such situation, not only the quality of care affected, the probability of complications such as the moral distress increases in doctors and nurses (12). In the study of Asterk (2003), the highest average is belonging to the "manager's factor" and the lowest is the "doctor's factor" (13). Which reveals a relatively similar pattern of organizational relationships between nurses and other colleagues in different cultures.…”
Section: Resultsmentioning
confidence: 77%
“…In such situation, not only the quality of care affected, the probability of complications such as the moral distress increases in doctors and nurses (12). In the study of Asterk (2003), the highest average is belonging to the "manager's factor" and the lowest is the "doctor's factor" (13). Which reveals a relatively similar pattern of organizational relationships between nurses and other colleagues in different cultures.…”
Section: Resultsmentioning
confidence: 77%
“…In a previous study, we investigated moral distress among Iranian physicians and compared the results to those of similar studies in other countries ( 5 ). It was found out that the physicians under study showed a high moral sensitivity, a moderate to high moral distress intensity and a low to moderate frequency of moral distress.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians are always exposed to moral distress due to some circumstances, such as taking action despite one’s conscience, not providing full treatment due to the financial weakness of a patient, ineffective treatment, lack of time, patients on a long waiting list, lack of resource and organizational factors ( 4 ). Our previous study found moral distress among Iranian physicians ( 5 ) ; the consequences are anger, hopelessness, depression, shamefulness, distress, sadness, disappointment and feeling miserable ( 6 , 7 ). Its long-term consequences emerge due to unresolved moral distresses, which are called moral residue.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted on medical students, facing good doctors and negative models caused increased and decreased interest into medical ethics, respectively. In fact, the physicians involved in teaching were viewed as models in medical ethics training, even if they were not teaching medical ethics [34,35]. In a qualitative study, students indicated role model as the greatest factor of learning professional ethics.…”
Section: Comprehensive Model-based Educational Systemmentioning
confidence: 99%